Building National Defense Awareness in Community to Improve Nationalism in Order to Prevent Nation Disintegration - Darmawan, Ade H; Sadipung, Theresia Oktavia (Dinasti International Journal of Management Science, 2025)
Developing an understanding of national defense among citizens is a very significant strategic step in strengthening the sense of nationalism and avoiding the disintegration of the nation. By instilling national defense values ??such as love for the country, loyalty to Pancasila, and the spirit of unity, the main goal is to form a strong national society that is ready to contribute to national stability. This development aims to produce people who have a sense of responsibility towards the country and master their position in protecting national unity. The approach used in this training includes guidance, socialization and ongoing training. With this approach, it is hoped that citizens can deeply understand the meaning of unity and the position of each person in protecting national stability. This explanation aims to build collective understanding, which means reducing threats to the nation's integrity. With solid cooperation, fostering understanding of national defense can produce strong national resilience and reduce the risk of division, let alone disintegration of the nation.